A History of the Concepts Experience and Experiment in Russian Culture. Issue 1 (1st June 2022) - Smirnova, Ekaterina
Abstract: Why, for a long time, was there no linguistic means to distinguish between the concepts experience and experiment in many European languages, such as Italian, French, and Russian? Was the Russian case influenced by French culture? This article addresses these issues. The most important finding of the study is that no idea of personal experience existed in Russian literature before the second half of the eighteenth century, and the word opyt was later borrowed from the scientific lexicon for expressing the meaning of experience. This is the opposite of what happened in other European languages. This suggests that the concept of experiment is more basic in the Russian mentality. Experience grows from experiment but not vice versa. All these aspects of the semantic history of "experiment" and "experience" are illustrated with extensive textual citations found in the Russian National Corpus and in the electronic library of Institute of Russian Literature.